FISHERIES EXTENSION STRATEGY FOR INDEPENDENT COMMUNITY DEVELOPMENT IN TANAH DATAR REGENCY, WEST SUMATERA PROVINCE - Nindy Dwi Putri; Kusai Kusai; Viktor Amrifo (Berkala Perikanan Terubuk, 2021)
This research was carried out in December 2020 at the Food and Fisheries Service ofWest Sumatra Province. This study aims to find out how the strategies used by extensionworkers in forming independent target groups in the midst of the many problems thatoccur in the community in Tanah Datar Regency. The method used in this study is asurvey method with a descriptive qualitative approach with a phenomenologicalconcept. The total population in this study were 5 respondents and 6 informants.From the results of the study, it was found that the strategies carried out by extensionworkers in Tanah Datar Regency can be seen from 5 indicators, namely approach,counseling, coaching, training, and evaluation. The forms of approach taken by theextension worker to the community are the mass approach, the group approach, and theindividual approach. Extension officers conduct counseling to community groups aimedat increasing public knowledge about the material being taught. Extension workers alsocarry out coaching in stages, this aims to increase public knowledge and provideexamples of how to do cultivation. In addition to coaching the extension workers, theyalso make useful trainings to increase the skills of the community and they can managetheir own cultivation well. After everything is running, the extension worker evaluateswhat the community lacks and must be done to increase independence in people's livesin Tanah Datar Regency.